2012
DOI: 10.1123/jab.28.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Walking on High Heels Changes Muscle Activity and the Dynamics of Human Walking Significantly

Abstract: The aim of the study was to investigate the distribution of net joint moments in the lower extremities during walking on high-heeled shoes compared with barefooted walking at identical speed. Fourteen female subjects walked at 4 km/h across three force platforms while they were filmed by five digital video cameras operating at 50 frames/second. Both barefooted walking and walking on high-heeled shoes (heel height: 9 cm) were recorded. Net joint moments were calculated by 3D inverse dynamics. EMG was recorded f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
74
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 30 publications
(54 reference statements)
12
74
2
4
Order By: Relevance
“…For instance, when high-heeled shoes force the foot into a fixed plantar-flexed position (thus preventing it from extending the leg to produce the preemptive push-off), the only joint in the sequence available to compensate appears to be the lower lumbar spine, where tilting of the pelvis effectively extends the support leg relative to the CoM. There is substantial direct evidence that plantar flexor moment is severely reduced when high-heeled shoes are worn, but the GRF profile remains quite similar to low-heeled or unshod walking (Simonsen et al, 2012). Opila-Correia (1990) reported that there was no significant difference in pelvic motion between participants wearing low and high heels; however, speed and step length were reduced in highheeled walking.…”
Section: Abstract Locomotion Walking Task Constraint Economymentioning
confidence: 84%
“…For instance, when high-heeled shoes force the foot into a fixed plantar-flexed position (thus preventing it from extending the leg to produce the preemptive push-off), the only joint in the sequence available to compensate appears to be the lower lumbar spine, where tilting of the pelvis effectively extends the support leg relative to the CoM. There is substantial direct evidence that plantar flexor moment is severely reduced when high-heeled shoes are worn, but the GRF profile remains quite similar to low-heeled or unshod walking (Simonsen et al, 2012). Opila-Correia (1990) reported that there was no significant difference in pelvic motion between participants wearing low and high heels; however, speed and step length were reduced in highheeled walking.…”
Section: Abstract Locomotion Walking Task Constraint Economymentioning
confidence: 84%
“…This fact may be related to the increased external knee adduction moment due to the use of high heels 2,21 . With the objective to confront the external adduction moment, the quadriceps muscle, by contracting, generates an internal abduction moment 20 . However, a major increase in the internal moment caused by the muscles of the lateral side o the knee could also increase the lateral slide of the patella 2 .…”
Section: Discussionmentioning
confidence: 99%
“…By observing the higher incidence of PFPS among females, and knowing that the use of high-heeled shoes could trigger changes in the musculoskeletal system in response to biomechanical changes in the lower limbs 3 , researchers developed studies that assessed the effect of high heels in the muscular activity 3 , as well as in biomechanics and kinetics variables of the lower limb 19,20 . Ho et al 19 verified that the high-heeled shoes increase the stress of the patellofemoral joint due to the increased knee extensor moment, while Simonsen et al 20 demonstrated that high heels cause the knee abduction moment to increase. According to these authors, the changes in the internal moments both in the sagittal and in the frontal planes would be related to the increased EMG activity of the extensor muscles of the knee, and with the greater stress over the patellofemoral joint, resulting from changes in the patellar movement.…”
Section: Introductionmentioning
confidence: 99%
“…Other related symptoms can be present in the lower back, hip joints, etc. With prolonged wear, permanent changes in posture (Silva, Siqueira, & Silva, 2013) and walking patterns can occur (Blanchette, Brault, & Powers, 2011;Simonsen et al, 2012;Chien, Lu, & Liu, 2013;Cronin, 2014). Frequent wears can experience a permanent shortening or decreased function of the Achilles tendon and gastrocnemius muscles (Csapo, Maganaris, Seynnes, & Narici, 2010).…”
mentioning
confidence: 99%